Exact solitons, periodic peakons and compactons in an optical soliton model. Issue 2 (January 2018) - Zhang, Tonghua; Li, Jibin
Abstract To study the properties of one-dimensional spatial solitons in thermal nonlocal media, we investigate the dynamical behaviour and bifurcation of solutions of the planar systems deduced from the model for one-dimensional beams. By approach of dynamical systems, we obtain the exact forms of parametric representations for solitary wave solution, kink wave solution, periodic wave solution, periodic peakon and compacton solution. Different wave profiles have been recovered by using the associated planar dynamical systems, showing new types of wave solutions which have not been observed in previous studies for the similar models.